Die Apostelgeschichte und die hellenistische Geschichtsschreibung : Festschrift für Eckhard Plümacher zu seinem 65. Geburtstag - Plümacher, Eckhard.; Breytenbach, Cilliers, 1954-; Schröter, Jens, 1961- (Ancient Judaism and Early Christianity, 2004)
This volume - a Festschrift in honour of the renowned Acts-scholar Eckhard Plümacher - contains thirteen articles on Luke's Acts of the Apostles. Presented are essays concerning Luke's language and style (Alexander, Koch, Steyn, Victor), the literary and historiographical technique applied in Acts (Moessner, Koch, Lindemann), on Luke's theology / Christology (Schröter, Vouga) and on the use (and abuse) of Acts for reconstructing aspects of the history of Early Christianity (Breytenbach, Horn, Schmithals) and for constructing theology relevant to modern culture (Vouga). Furthermore it contains a critical edition and commentary of the Martyrdom of Stephen with a discussion of its relationship to Acts (Bovon/Bouvier) and a presentation and discussion of some unknown Coptic Fragments of Acts (Bethge).